2020
DOI: 10.1080/13696998.2020.1819822
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of osimertinib for first-line treatment of locally advanced or metastatic EGFR mutation positive non-small cell lung cancer in Singapore

Abstract: Objective: Non-small cell lung cancer (NSCLC) accounts for 80-90% of all lung cancer cases and is usually associated with a poor prognosis. However, targeted therapy with first and second generation tyrosine kinase inhibitors (TKIs) has so far improved progression-free survival of epidermal growth factor receptor (EGFR) mutant NSCLC patients. Osimertinib, a third generation EGFR TKI has recently shown improved overall survival of 6.8 months in previously untreated EGFR mutant NSCLC patients. We assessed the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Nevertheless, the ICER is already very close to the WTP of China in our study, indicating appropriate price reduction may make osimertinib cost-effective. Our results are in accordance with economic evaluations in other countries comparing first-line osimertinib, gefitinib, or afatinib in advanced EGFR-mutated NSCLC, which may help clinicians and administrators determine the preferred economic treatment strategy ( Aziz et al, 2020 ; Khoo and Gao, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, the ICER is already very close to the WTP of China in our study, indicating appropriate price reduction may make osimertinib cost-effective. Our results are in accordance with economic evaluations in other countries comparing first-line osimertinib, gefitinib, or afatinib in advanced EGFR-mutated NSCLC, which may help clinicians and administrators determine the preferred economic treatment strategy ( Aziz et al, 2020 ; Khoo and Gao, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, the acceptable cost-effectiveness could be significantly improved when the cost of osimertinib was reduced by 25%, which was consistent with our results and those of Aguiar et al (2018) . Similarly, the ICER values of SG$418,839/QALY and A$432,197/QALY for osimertinib vs. first-generation EGFR-TKIs in first-line therapy with advanced EGFR-mutant NSCLC in Singapore and Australia were obtained, respectively, which was higher than the then WTP (SG$100,000/QALY and A$50,000/QALY, respectively), revealing to be not cost-effective ( Aziz et al, 2020 ; Khoo and Gao, 2021 ). Another Markov analysis published in Spain indicated a similar cost-effectiveness as compared to first-generation EGFR-TKI because ICER (€273,895.36/QALY) was higher than the commonly accepted threshold €24,000/QALY of Spain while a discount of more than 60% was a cost-effective option ( Aguilar-Serra et al, 2019 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the economic evaluations were used to directly support decisions regarding reimbursement via HTA documents ( n = 20) [ 69 – 88 ]. For the remainder, studies stated that the use was for policy/funding decisions ( n = 5) [ 34 , 35 , 48 , 56 , 62 ], to promote the sustainability of limited healthcare resources ( n = 5) [ 30 32 , 60 , 61 ], or to support treatment choices ( n = 7) [ 39 , 47 , 50 , 55 , 57 , 59 , 65 ]. Twenty-two studies did not explicitly state the intended use of the economic evaluations [ 33 , 36 38 , 40 46 , 49 , 51 54 , 58 , 63 , 64 , 66 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, EGFR-TKI as rst-line treatment has multiple treatment options in real-world setting (Hayashi et al 2022;How et al 2022), and treatment decisions mainly depend on the characteristics of tumors and the feasibility based on patient-related factors, particularly with regards to cost-effectiveness in clinical practice. Pharmacoeconomic studies suggest that rst-line rst-generation EGFR-TKI and gene-guided osimertinib second-line strategy was more cost-effective than osimertinib rst-line treatment (Ezeife et al 2018;Aziz et al 2020; Khoo et al 2021;Cai et al 2019). In addition, APPLE trial (Remon et al 2023) updated data and showed comparable OS between rst-line osimertinib versus ge tinib followed by osimertinib in European Lung Cancer Congress 2023.…”
Section: Introductionmentioning
confidence: 99%